Sustainable solutions to antibiotic resistance: a comprehensive review of plant-derived carbon dots and phytochemicals as innovative antibacterial agents - Sewara J. Mohammed; Awat S. Mohammed; Dlzar D. Ghafoor; Hastyar H. Najmuldeen; Aya I. Tamar; Danyar D. Jalal; Fayez Alghofaili; Dana A. Kader; Rebaz F. Hamarawf; Kawan F. Kayani (Phytochemistry Reviews, 2026)

Effects of different soybean protein sources on growth performance, feed utilization efficiency, intestinal histology, and physiological gene expression of Pacific white shrimp (Litopenaeus vannamei) in green water and indoor biofloc system. - Khanh Q. Nguyen; Aya S. Hussain; Adela N. Araujo; Leila M. Strebel; Trenton L. Corby; Melanie A. Rhodes; Timothy J. Bruce; Jorge Cuéllar-Anjel; D. Allen Davis (Aquaculture, 2026)

Efficacy of yeast-mediated SeNPs on gastric ulcer healing and gut microbiota dysbiosis in male albino rats - Aya Adel Fath-All; Tarek Atia; Ayman Saber Mohamed; Neveen M. Khalil; Tamer D. Abdelaziz; Neamat A. Mahmoud; Abdallah Mohammed Elagali; Hader I. Sakr; Mohamed N. Abd El-Ghany (Tissue and Cell, 2025)

Corrigendum correction to: Tessier et al. 2024 “Heng-o Corona, Venus: Dyke swarms record evolution of its underlying mantle plume” Icarus 417 (2024) 116090, https://doi.org/10.1016/j.icarus.2024.116090 - Aya D. Tessier; Richard E. Ernst; Hafida El Bilali (Icarus, 2025)

Heng-o Corona, Venus: Dyke swarms record evolution of its underlying mantle plume - Aya D. Tessier; Richard E. Ernst; Hafida El Bilali (Icarus, 2024)

Microbial Study with Mathematical and Statistical Modelling for Synchronous Biotreatment of Actual Restaurant Wastewater and Bioelectricity Recovery in Microbial Fuel Cell - Ahmed Y. Radeef; Aya A. Najim; Mustafa A. Kareem; Hashem E. Hashem; Ammar D. Zaidan (Indian Journal of Microbiology, 2024)

Synthesis, urease inhibitory and anticancer evaluation of glucosamine-sulfonylurea conjugates - Ghadeer A. R. Y. Suaifan; Mayadah Shehadeh; Dua’a Tahboub; Aya A. M. Mohammed; Michael D. Threadgill; Anand Gaurav; Majid Khan (Medicinal Chemistry Research, 2024)

An integrated novel plasma-microalgae approach for landfill leachate treatment using a high-ammonia tolerant strain of Chlorella vulgaris - Aya T. Farag; Thomas D. Holmes; D. James Gilmour; William B. Zimmerman (Algal Research, 2024)

Process assessment of renewable-based acrylic acid production from glycerol valorisation - Aya Sandid; Jesús Esteban; Carmine D'Agostino; Vincenzo Spallina (Journal of Cleaner Production, 2023)

Temporal dynamics of total and bioavailable fungicide concentrations in soil and their effect upon nine soil microbial markers - Judith Riedo; Aya Yokota; Barbara Walther; Nora Bartolomé; Marcel G.A. van der Heijden; Thomas D. Bucheli; Florian Walder (Science of The Total Environment, 2023)

Passive acoustic feeders as a tool to assess feed response and growth in shrimp pond production - João Reis; Aya S. Hussain; Alexis Weldon; Samuel Walsh; William Stites; Melanie Rhodes; D. Allen Davis (Aquaculture International, 2023)

New records of rare species in the Mediterranean Sea (December 2022) - FEDERICA MONTESANTO; MARCO ALBANO; DΕΝΙΖ AYAS; FEDERICO BETTI; GIOELE CAPILLO; MELIH ERTAN ÇINAR; MARIA CORSINI-FOKA; FABIO CROCETTA; ERTAN DAĞLI; CLAUDIO D’IGLIO; MARKOS DIGENIS; BRANKO DRAGIČEVIĆ; et al. (Mediterranean Marine Science, 2022)
This Collective Article presents information on 20 taxa belonging to five (5) Phyla: Cnidaria (2), Mollusca (8), Arthropoda (4), Echinodermata (1) and Chordata (5) recorded from the Alboran Sea to the Levantine Sea. These new records were found in seven (7) different ecoregions as follows: Alboran Sea: new record of the rare football octopus Ocythoe tuberculata in the harbour of Algeciras (Spain); Western Mediterranean Sea: first record of the isopod Arcturinella deltensis in the Ligurian Sea, and the third in the whole Mediterranean Sea; third Mediterranean site for the Muricidae Coralliophila ahuiri along the Italian coasts (Alghero); first and westernmost record of the goby Corcyrogobius liechtensteini from the Iberian Peninsula; new record of the sea slug Glaucus atlanticus from the coast of the Iberian Peninsula; first and easternmost record of Holothuria (Vaneyothuria) lentiginosa lentiginosa along the Italian coasts; Tunisian Plateau/Gulf of Sidra: seventh record of the oceanic squid Thysanoteuthis rhombus in Tunisia, and first for the Gulf of Gabes. Ionian Sea: second occurrence of the Atlantic tripletail Lobotes surinamensis in the Ionian Sea and first record from the Strait of Messina area; new record of the rare sea elephant Pterotrachea coronata from the Strait of Messina; Adriatic Sea: first record of a facies of football ascidian Diazona violacea in the South Adriatic Sea (Tremiti Island, Italy); two records of the sevengill shark Heptranchias perlo in Croatian waters after more than 70 years of absence of documented records in this area; first known occurrence of the nudibranch Jalonus hyalinus in Slovenian waters and also the first known occurrence of this species in the Adriatic Sea; first record of the nudibranch Okenia elegans in Slovenian waters; Aegean Sea: First record of the parasitic isopod Nerocila milesensis along Greek coasts (Crete island) as well as the second record worldwide; additional record of the brachyuran Paragalene longicrura collected from the Saronikos Gulf (Greece); first record of the siphonophore Rhizophysa filiformis in Greek waters as well as the second record of this species in the eastern Mediterranean basin; new record of the rare and protected angelshark Squatina aculeata along Turkish coasts; Levantine Sea: first record of the marine amphipod Caprella andreae in the Levantine Mediterranean shore of Israel, based on both morphological and molecular data; first occurrence of the cephalopod Tremoctopus violaceus along Turkish coasts, which confirms its presence in the north-eastern coasts of Turkey; record of a bloom of the thermophilic jellyfish Pelagia noctiluca in the north Levantine Sea.

Correction to: Electrochemical mineralization of abattoir wastewater with continuous system - D. Ozturk; A. E. Yilmaz; Z. Sapci Ayas (International Journal of Environmental Science and Technology, 2022)

Granulocyte colony-stimulating factor (G-CSF) enhances cocaine effects in the nucleus accumbens via a dopamine release–based mechanism - Lillian J. Brady; Kirsty R. Erickson; Kelsey E. Lucerne; Aya Osman; Drew D. Kiraly; Erin S. Calipari (Psychopharmacology, 2021)

Electrochemical mineralization of abattoir wastewater with continuous system - D. Ozturk; A. E. Yilmaz; Z. Sapci Ayas (International Journal of Environmental Science and Technology, 2021)

Low-Cost Intervention to Increase Influenza Vaccination Rate at a Comprehensive Cancer Center - Petros D. Grivas; Sumana Devata; Rami Khoriaty; Philip S. Boonstra; Joshua Ruch; Kevin McDonnell; Leonel Hernandez-Aya; Joshua Wilfong; Jeffrey Smerage; Michael G. Ison; Joseph N. S. Eisenberg; Maria Silveira; et al. (Journal of Cancer Education, 2017)

New Mediterranean Biodiversity Records (March 2016) - P. K. KARACHLE; A. ANGELIDIS; G. APOSTOLOPOULOS; D. AYAS; M. BALLESTEROS; C. BONNICI; M. M. BRODERSEN; L. CASTRIOTA; N. CHALARI; J. M. COTTALORDA; F. CROCETTA; A. DEIDUN; et al. (Mediterranean Marine Science, 2016)
In this Collective Article on “New Mediterranean Biodiversity Records”, we present additional records of species found in the Mediterranean Sea. These records refer to eight different countries throughout the northern part of the basin, and include 28 species, belonging to five phyla. The findings per country include the following species: Spain: Callinectes sapidus and Chelidonura fulvipunctata; Monaco: Aplysia dactylomela; Italy: Charybdis (Charybdis) feriata, Carcharodon carcharias, Seriola fasciata, and Siganus rivulatus; Malta: Pomacanthus asfur; Croatia: Lagocephalus sceleratus and Pomadasys incisus; Montenegro: Lagocephalus sceleratus; Greece: Amathia (Zoobotryon) verticillata, Atys cf. macandrewii, Cerithium scabridum, Chama pacifica, Dendostrea cf. folium, Ergalatax junionae, Septifer cumingii, Syphonota geographica, Syrnola fasciata, Oxyurichthys petersi, Scarus ghobban, Scorpaena maderensis, Solea aegyptiaca and Upeneus pori; Turkey: Lobotes surinamensis, Ruvettus pretiosus and Ophiocten abyssicolum. In the current article, the presence of Taractes rubescens (Jordan & Evermann, 1887) is recorded for the first time in the Mediterranean from Italy. The great contribution of citizen scientists in monitoring biodiversity records is reflected herein, as 10% of the authors are citizen scientists, and contributed 37.5% of the new findings.

Seasonal gonad cycle of the climbing perch Anabas testudineus (Teleostei: Anabantidae) in a tropical wetland - Rieziel Ann D. Bernal; Frolan A. Aya; Evelyn Grace T. De Jesus-Ayson; Luis Maria B. Garcia (Ichthyological Research, 2015)

Determination of coastal border line: an integrated approach for a part of Antalya coast (Turkey) - C. Gokceoglu; H. A. Nefeslioglu; D. Turer; A. Akgun; Z. Ayas; M. Temimhan (Arabian Journal of Geosciences, 2015)

Sequence Variants in SLC6A3, DRD2, and BDNF Genes and Time to Levodopa-Induced Dyskinesias in Parkinson’s Disease - Natalie Kaplan; Aya Vituri; Amos D. Korczyn; Oren S. Cohen; Rivka Inzelberg; Gilad Yahalom; Evgenia Kozlova; Roni Milgrom; Yael Laitman; Eitan Friedman; Saharon Rosset; Sharon Hassin-Baer (Journal of Molecular Neuroscience, 2014)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).